Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsenergylett.8b02043
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Electronic Conductivity within Secondary Particles Revealing a Capacity-Fading Mechanism of Layered Ni-Rich Cathode

Abstract: A remarkable reduction in electronic conductivity in the core region rather than on the surface of secondary particles is proposed as a capacity-fading mechanism of a Ni-rich cathode. This result is confirmed by analyzing the electronic conductivity of the secondary particles of Li[Ni 0.98 Co 0.01 Mn 0.01 ]-O 2 using the scanning spreading resistance microscopy (SSRM) mode of atomic force microscopy. SSRM analysis reveals that a much thicker rocksalt phase, which is transformed from the original layered struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 25 publications
4
88
0
Order By: Relevance
“…The appearance of distinct cracks, even after the first discharge, in NCA80 for all‐solid‐state cells (Figure 3d) is not common for Ni‐rich cathode materials in LIBs using LEs . Although the uniaxially applied pressure is released after the cold‐pressing process, any stresses may remain locally due to elastic and plastic deformation of the SEs .…”
Section: Resultsmentioning
confidence: 97%
“…The appearance of distinct cracks, even after the first discharge, in NCA80 for all‐solid‐state cells (Figure 3d) is not common for Ni‐rich cathode materials in LIBs using LEs . Although the uniaxially applied pressure is released after the cold‐pressing process, any stresses may remain locally due to elastic and plastic deformation of the SEs .…”
Section: Resultsmentioning
confidence: 97%
“…Looking at the market trends for commercial LIBs, the use of Ni‐rich cathodes is mandatory for increasing the energy density of a Li/NCM battery . However, a reactive Ni 4+ in Ni‐rich cathodes at a delithiated state usually incurs extensive surface damage by forming a NiO‐like rock‐salt structure, and simultaneously accelerates the electrolyte consumption . For the successful operation of a Li/Ni‐rich NCM battery, therefore, stabilization of the Ni‐rich cathode/electrolyte interface is as important as the stabilization of the Li‐metal anode/electrolyte interface.…”
Section: Resultsmentioning
confidence: 99%
“…However, developing a practical Li metal battery with Ni‐rich NCM cathode (Li/Ni‐rich NCM battery) has been hampered by the inferior cycling stability and poor safety of the Li‐metal anode; these limitations are mainly related to the high reactivity of Li with the electrolyte components as well as the uncontrollable growth of Li dendrites . In addition, at the cathode side, aggressive surface reaction of the Ni‐rich NCM cathode with the electrolyte solution accelerates the degradation of the cathode surface, and subsequently yields an electrochemically inactive NiO‐like rock‐salt structure . These undesirable surface chemistries on the Li metal anode and Ni‐rich cathodes lead to continuous electrolyte consumption, eventually limiting the lifetime of the Li/Ni‐rich NCM battery.…”
Section: Introductionmentioning
confidence: 99%
“…[67] Copyright 2018, Royal Society of Chemistry; Copyright 2018, American Chemical Society. [68] (Figure 12b). A precise control on the sintering conditions has led to optimal LiNi0.70Co0.15Mn0.15O2 cathodes with a low cationic disordering and high reversible capacity (Figure 12c).…”
Section: Synthetic Controlmentioning
confidence: 99%
“…have recently used scanning spreading resistance microscopy (SSRM) mode of atomic force microscopy to analyze the electronic conductivity of the secondary particles of LiNi 0.98 Co 0.01 Mn 0.01 O 2 (Figure 11e). [ 68 ] They found that transformation of layered to rock salt phase occurred intensively in the core region of LiNi 0.98 Co 0.01 Mn 0.01 O 2 cathode, which may be because the core region has lower Li concentration, larger surface area and higher surface energy of the primary particles as well as higher internal stress. Such rock salt layer would cause a significantly decreased electronic conductivity, leading to sluggish Li insertion/extraction kinetics.…”
Section: The Degradation Pathway Of Ni‐rich Layered Cathodes Under Hamentioning
confidence: 99%